A new genus and species of tanager (Passeriformes, Thraupidae) from the lower Yungas of western Bolivia and southern Peru. Issue 4 (29th October 2021) - Lane, Daniel F; Aponte Justiniano, Miguel Angel; Terrill, Ryan S; Rheindt, Frank E; Klicka, Luke B; Rosenberg, Gary H; Schmitt, C Jonathan; Burns, Kevin J
Abstract: We describe a colorful and distinctive new species of tanager from the lower slopes of the Andes of southeastern Peru and western Bolivia. The species was first noted from southeastern Peru in 2000, but little of its natural history was uncovered until the 2011 discovery of a breeding population in deciduous forest in an intermontane valley, the Machariapo valley, in Bolivia. This species appears to be an intratropical migrant, breeding in deciduous forest during the rainy season (November–March) and spending the dry season dispersed along the lower slopes of the Andes, apparently favoring Guadua bamboo-dominated habitats in both seasons. Phylogenetic evidence suggests this tanager is embedded within a clade of thraupids that includes Ramphocelus, Coryphospingus, Loriotus, Tachyphonus, and related genera in the subfamily Tachyphoninae. Within this subfamily, the new species falls in a clade with two monotypic genera, Eucometis penicillata (Gray-headed Tanager) and Trichothraupis melanops (Black-goggled Tanager). There is strong support for a sister relationship between the new tanager and T. melanops, but because all three species in this clade are highly distinctive phenotypically, we propose erecting a new genus and species name for the new tanager. Graphical Abstract: Lay Summary: We discovered a new species of tanager, from the foothills of the Andes mountains in Peru and Bolivia, which we name the Inti Tanager. The name "Inti" is the Quechua (a language indigenous to the region) word that means "sun, " referring to the bright yellow color of the bird. Unlike most new bird species discovered recently, which typically differ only subtly from their closest relatives, this species is so different in appearance and genetics that we also described a new genus just for it. The tanager family, to which the new species belongs, is one of the largest bird families in the world (with about 377 species), restricted almost entirely to the American tropics and including many beautifully colorful species. We uncovered a surprising piece of natural history about the Inti Tanager: it migrates from its breeding grounds in a little-explored valley in Bolivia to "winter" along the lower slopes of the Andes in Peru. Such migration within the tropics is rare within the tanagers. That this unique, bright yellow bird could have gone unnoticed by ornithologists until recently attests to the remoteness of the areas where it lives and to the importance of continued biological surveys off-the-grid in South America.